Penerapan Model PBL Berbasis Website Magma Indonesia terhadap Kemampuan Berpikir Spasial - Pamuji, Riski Indah; Pangastuti, Era Iswara; Kurnianto, Fahmi Arif; Astutik, Sri; Mujib, Muhammad Asyroful (Universitas Pendidikan Ganesha, 2025)
Spatial thinking skills are a crucial competency in observing, analyzing, and describing geospheric phenomena. However, field observations show that teachers still rely on lecture-based methods and rarely utilize innovative media. This study aims to analyze students' spatial thinking skills through the implementation of a Problem-Based Learning (PBL) model based on the Magma Indonesia website. The research was conducted at MAN 2 Jember on the topic of disaster mitigation and adaptation. The sample consisted of two classes: XI K as the experimental class using the PBL model, and XI J as the control class using the Discovery Learning model. The research method employed was a quasi-experimental design using a post-test only control group design. The results showed that the average spatial thinking test score in the experimental class was 81.7, outperforming the control class, which scored 65.1. Hypothesis testing using the t-test produced a significance value of 0.00, which is less than 0.05. The study concludes that there is a significant effect of implementing the PBL model based on the Magma Indonesia website on students' spatial thinking skills.